PENGARUH MODEL ACTIVE LEARNING TIPE CARD SORT TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 160 BARRU - Anisa Putri; Haerul Syam, Sirajuddin (STKIP Subang, 2025)
The main problem in this study is the learning process that is not optimal so that it has an impact on the low learning outcomes of students' mathematics, which is marked by the acquisition of students' daily mathematics test results where only 1 person reaches the minimum completeness criteria (KKM). In addition, the teacher has not used a varied learning model so that students' learning outcomes are low. This study aims to determine the effect of the Card sort type Active Learning model on the mathematics learning outcomes of fourth grade students of SDN 160 Barru. This study used a Quantitative research method pre-experimental design with a one-group pretest-posttest design model. Pretest was carried out before being given treatment to see the initial ability of students, after being given treatment in the form of an Active Learning type Card Sort model, a posttest was carried out to see the learning outcomes after being given treatment. The samples in this study were 10 fourth grade students of SDN 160 Barru. Data obtained through pretest-posttest and observation were then analyzed descriptively and inferentially. The results showed that the application of the Card Sort type of Active Learning model had a significant effect on the learning outcomes of mathematics class IV SDN 160 Barru. In the pretest, the average student score was 54.5 with a 10% completeness rate. While in the posttest, the average student score increased to 82.8 with a 100% completion rate. Observations also showed that students were more active in the learning process. Based on these results, it can be concluded that the application of the Card Sort type Active Learning model has an effect in improving the mathematics learning outcomes of fourth grade students of SDN 160 Barru